Al2O3 sintered pellets as thermoluminescent dosimeters (2012)
Verification of the radiation dose received by the area exposed during medical treatment is essential for the evaluation of any radiotherapy regimen.This work describes the thermoluminescent (TL) characteristics of sintered Al2O3 tablets, for possible use as a low dose dosimeter dose. Al2O3 tablets sintered under different calcination conditions, with a diameter of 5 mm and a thickness of 1 mm, were irradiated at different doses using a 60Co Theratron 780Cr enaire unit at room temperature. The reading was done on a Harshaw TLD 4500.The main dosimetric properties of the material (brightness curve, response reproducibility, reuse, linearity and thermal decay) have been studied in detail. The brightness curve of the Al2O3 sintered pellets has an intense TL peak around 165C, which can be used for dosimetry. The results show that the pills can be used in quality control programs such as a thermoluminescent dosimeter in the therapeutic dose range. The importance of this work is that aluminum oxide (−Al2O3) is a promising alternative within TL materials used for “in vivo” dosimetry within quality control programs.